DAMPAK PERNIKAHAN DINI TERHADAP KEBERLANGSUNGAN PENDIDIKAN AGAMA ISLAM DI DESA LAU REMPAK DUSUN II LAU BINTANG KEC. STMM HILIR KAB. DELI SERDANG SUMATERA UTARA T.A 2021/2022 - Parlaungan Lubis, Nahdia Suhaila, Ramlan Padang, (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
Marriage is sunatullah that generally applies to all creatures, marriage is a path chosen by Allah SWT as a way for his creatures to reproduce. In the context of carrying out the educational process between husband and wife, they must have "supplies" in forming religious beliefs for their families and children. For this reason, understanding Islamic religious education is the basis for realizing a real marriage. This study aims to determine whether or not there is an impact of early marriage on the sustainability of Islamic religious education in Lau Rempak Village, Dusun II Lau Bintang Kec. STM downstream Kab. Deli Serdang. The test was carried out with a "t" test analysis to determine whether there was an impact of early marriage on the sustainability of Islamic religious education. The test criteria is to compare the value of tcount with the value of ttable at the 95% significance level, with an error of 0.05%, the degrees of freedom are n-2 or 15-2 = 13. And the results obtained are tcount = 0.46116 ttable = 2160 which it means that Ho is accepted, which means that there is an impact of early marriage on the sustainability of Islamic religious education in Lau Rempak Village, Dusun II Lau Bintang, Kec. STM Hilir Kab. Deli Serdang.